2013
DOI: 10.1080/08870446.2013.859257
|View full text |Cite
|
Sign up to set email alerts
|

Psychological intervention with couples coping with breast cancer: A systematic review

Abstract: Objective: Information about psychological intervention with couples coping with breast cancer is not well-disseminated. This can be explained, at least in part, by the absence of knowledge about the efficacy of this kind of intervention. The aim of the present systematic review is to identify and describe psychological interventions for couples coping with breast cancer and evaluate their efficacy. Results: Of 129 abstracts, 13 were extracted for further analysis and a final ten studies were deemed eligible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 47 publications
1
68
0
3
Order By: Relevance
“…The majority of existing couples interventions are among cancer populations. Such studies have demonstrated positive effects on physical, interpersonal, and emotional outcomes among couples living with cancer [27,28,29]. Other systematic review work exploring the benefits of couples interventions in coronary heart disease, has shown significant improvements on quality of life and blood pressure in patients, and depression in both patients and partners [30].…”
Section: Couples Interventionsmentioning
confidence: 99%
“…The majority of existing couples interventions are among cancer populations. Such studies have demonstrated positive effects on physical, interpersonal, and emotional outcomes among couples living with cancer [27,28,29]. Other systematic review work exploring the benefits of couples interventions in coronary heart disease, has shown significant improvements on quality of life and blood pressure in patients, and depression in both patients and partners [30].…”
Section: Couples Interventionsmentioning
confidence: 99%
“…In particular, our objectives were the following: (1) To explore and analyze the psychological variables, such as attachment, quality of life, depression, and anxiety, that can contribute to the implementation of a functional process of adjustment to the disease and promote better psychological well-being. (2) To understand whether the attachment dimension is associated with couple satisfaction (it has been found that cancer patients' and their spouses' anxious and avoidant attachment styles are positively correlated with a marital dissatisfaction [3] ). (3) To verify whether the level of anxiety and depression of each couple affected couple satisfaction.…”
mentioning
confidence: 99%
“…As relações conjugais podem sair reforçadas ou deterioradas. A diminuição da auto-estima, na mulher mastectomizada, repercute-se na auto-imagem, afectando a sexualidade e, por consequên-cia a relação com o companheiro (27). A vida muda por completo após um diagnóstico de cancro.…”
Section: Resultados Obtidos Na Categorização Conceptual Na Categorizunclassified